Grounding heritage, sustaining identity: the recontextualization of kupatan jalasutra in Tanah Geseng, Bantul - Heri Priyatmoko; S.R.L Aji Sampurno; Indra Fibiona (Gelar: Jurnal Seni Budaya, 2026)
The Kupatan Jalasutra ritual in Srimulyo Village, Bantul, Yogyakarta, represents a form of living heritage rooted in the sacred landscape of Tanah Geseng, the burial site of Sunan Geseng. Previous studies have primarily examined the tradition as a cultural attraction, social ritual, or repository of local values, while limited attention has been given to its contemporary recontextualization as a mechanism for cultural identity formation and environmental stewardship. This study explores the historical continuity, symbolic meanings, and adaptive functions of the ritual in contemporary society. Employing an integrated historical ethnographic approach, the research combines critical analysis of local manuscripts and chronicles with participant observation, in depth interviews, and documentation. Data were analyzed through historical interpretation and grounded theory coding, supported by triangulation and member checking. The findings reveal that Kupatan Jalasutra functions as a dynamic cultural system integrating collective memory, Javanese Islamic spirituality, social solidarity, and ecological ethics. Symbolic interpretations of ketupat reinforce values of reconciliation, generosity, and social harmony, while communal practices such as village cleaning, sacred-site maintenance, and the use of local resources embody indigenous environmental ethics. The study argues that the resilience of Kupatan Jalasutra lies in its capacity to continuously adapt inherited traditions to contemporary social and environmental challenges without losing its symbolic foundations.